Asset Confiscation as a Criminal Policy against Proceeds of Corruption Crimes - I Putu Edi Rusmana; I Gusti Agung Kiddy Krsna Zulkarnain; I Gede Druvananda Abhiseka; Kadek Indra Dewan Tara (CV. Literasi Indonesia, 2026)
This research aims to analyze the concept of asset confiscation in corruption offenses and to examine its position within the criminal punishment system under Indonesian criminal law. Corruption is widely recognized as a crime that generates significant harm to state finances, governmental stability, and public trust in state institutions. In the development of modern criminal law, anti-corruption efforts are no longer solely oriented toward punishing offenders but also toward eliminating the economic benefits obtained from criminal activities through asset confiscation mechanisms. This study employs normative legal research using statutory and conceptual approaches. The legal materials consist of primary legal sources in the form of legislation related to corruption eradication and criminal procedure law, as well as secondary legal materials including academic literature, journal articles, and scholarly opinions relevant to asset confiscation and criminal policy. The findings reveal that asset confiscation in corruption cases should not merely be viewed as an additional punishment within the criminal sanction system, but also as a strategic instrument of criminal policy aimed at eliminating illicit economic gains while facilitating the recovery of state financial losses. Strengthening the mechanism of asset confiscation is therefore essential to enhance the effectiveness of anti-corruption policies and to ensure that corruption does not generate economic benefits for offenders.